Pendampingan Pengajuan Sertifikat Halal Produk Tempe dan Keripik Tempe pada UMKM Tempe Barokah Desa Kalensari Compreng - Fatimah, Nurlaeli; Fathurahman, Imron (LPPM STIE Hidayatullah Depok, 2024)
Kalensari Village is a village that is still rich in agriculture, and UMKM farming is still one of the livelihoods of Kalensari Village. Tempeh UMKM are processed products of the Kalensari community which have been developed to date, and have their own brand is tempe barokah. This community service will be carried out on February 3, 2024, which includes tempe UMKM actors. The first step in the process of applying for a halal certificate is by socializing with UMKM actors, observing the problems faced by UMKM actors, assisting in the implementation of submitting halal certificates. Based on the explanation above, it is stated that the submission of halal certificates is very important in compliance with the government, besides that the results of halal certificates for distribution permits can be a strategy to improve the quality and safety of tempeh products. The assistance carried out is expected to provide benefits for tempe barokah UMKM, and become an effort for other UMKM sectors.